Հայկական քառանիստ կոթողների թվագրման խնդիրը և Քասաղի խոյակը - Գրիգոր Գրիգորյան (ՀՀ ԳԱԱ հրատ.)
В исследованиях, посвященных ранним памятникам, бытует точка зрения, что по принятии Арменией христианства как государственной религии все без исключения памятники, в том числе стелы, были уничтожены. И дошедшие до нас четырехгранные пилоны с рельефами, как и изображения крестов на них, относятся к христианству. Исследование памятника приводит к следующим выводам. Независимо от того, языческие памятники разрушены христианами или временем, нельзя полностью отрицать их существование среди дошедших до нас фрагментов. In the studies on early monuments, the accepted viewpoint is that after adopting Christianity as state religion in Armenia, all pagan monuments, as well as steles, were indiscriminately destroyed and the surviving four-faced steles with sculptural reliefs, also all the crosses found on them, are Christian. The examination brings to the following conclusion: irrespective of the fact that pagan monuments might have been destroyed by Christians or ravaged by the time, it cannot be excluded that the fragments that have come down to us present parts of pagan steles. The cross inscribed into a circle was a sacred symbol for the pagans as well, and the presence of suchcrosses cannot be assumed as a basis to consider these steles Christian and date them accordingly.
Keywords: History; D History; N Fine Arts; NA Architecture